2004
DOI: 10.3168/jds.s0022-0302(04)73158-6
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices and Reported Antimicrobial Usage on Conventional and Organic Dairy Farms

Abstract: The primary objective was to compare reported antimicrobial usage between conventional and organic dairy farms. A secondary objective was to contrast selected management characteristics of conventional and organic dairy herds. A questionnaire was administered on site to selected dairy farmers located in Michigan, Minnesota, New York, and Wisconsin. Organic herds (n = 32) were smaller and produced less milk than conventional herds (n = 99). Lactating cows in organic dairies were more likely to be housed in tie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
196
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(215 citation statements)
references
References 5 publications
15
196
1
3
Order By: Relevance
“…Annual milk yields are significantly decreased under organic management, and we used a value 20% lower than that of conventional systems, based on reported reductions in yield ranging from 14.3% to 26.2% (43,44,67,68). Because of a paucity of available data, the proportion of heifers and dry cow equivalents within the herd was assumed to be equal to those reported for conventional production.…”
Section: Model 3 Dietary Guidelines For Americansmentioning
confidence: 99%
“…Annual milk yields are significantly decreased under organic management, and we used a value 20% lower than that of conventional systems, based on reported reductions in yield ranging from 14.3% to 26.2% (43,44,67,68). Because of a paucity of available data, the proportion of heifers and dry cow equivalents within the herd was assumed to be equal to those reported for conventional production.…”
Section: Model 3 Dietary Guidelines For Americansmentioning
confidence: 99%
“…The presence of deer on the farm has been associated with increased odds of being JD positive [79]. However, according to a study by Zwald et al [67], there is no difference in farmer reported contact rates with other farmed or wild animals between conventional and organic dairy farms. Nevertheless, it remains unclear how well rabbits or deer can be kept off the pastures at any time during the year.…”
Section: Nutritionmentioning
confidence: 69%
“…While there are many other reasons why producers convert to organic farming, some smaller farms might see an opportunity to avoid the consolidation process and increase farm income by converting to organic milk production. More recent reports demonstrate that organic farms tend to be smaller than conventional farms [7,8,67,68] (Figure 2). Small farms have been shown to have decreased odds of being JD positive [30,38] and, thus, smaller organic farms might have a reduced JD herd level prevalence compared to larger conventional farms.…”
Section: Farm Structurementioning
confidence: 99%
See 2 more Smart Citations